Genetic and healthy lifestyle factors in relation to the incidence and prognosis of severe liver disease in the Chinese population - Pang, Y; Lv, J; Kartsonaki, C; Yu, C; Guo, Y; Chen, Y; Yang, L; Millwood, IY; Walters, RG; Lv, S; Burgess, S; Sansome, S; et al. (Wolters Kluwer, 2023)
Background: Severe liver disease (SLD), including cirrhosis and liver cancer, constitutes a major disease burden in China. We aimed to examine the association of genetic and healthy lifestyle factors with the incidence and prognosis of SLD.